Nelida - Stern, Daniel, 1805-1876.; Hoggard, Lynn. (New York : State University of New York Press, 2003)
"First published in 1846 under the pen name Daniel Stern, Nelida tells the story of a beautiful French heiress who surrenders everything - marriage, reputation, and an aristocratic way of life - for the love of a talented young middle class painter. Based on this author's own ten-year relationship with the pianist and composer Franz Liszt, the novel quickly became the scandalous bestseller of its day. Its author, Marie d'Agoult, has emerged as one of the most remarkable women of her time. An aristocratic Parisian woman who left her husband and child to become the companion of Liszt, d'Agoult became an accomplished woman of letters whose works included a major history of the 1848 revolution in Paris. In Nelida, her only major novel, she brings to life the deeply intimate parts of her own story and the era in which it took place. Written with a keen sensitivity to social mores and psychological nuances, the novel reveals the primal cry of a woman determined to control her own destiny without betraying her womanhood."--Jacket
Intro -- Nelida -- Contents -- Illustrations -- Acknowledgments -- Prologue -- Nelida -- Epilogue -- Works Cited.
"Originally published in 1846 under the pen name Daniel Stern."
Includes bibliographical references (page 213).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Adultery -- France -- Fiction; Painters -- France -- Fiction; France -- Social life and customs -- 19th century -- Fiction; Peintres -- France -- Romans, nouvelles, etc; France -- Mœurs et coutumes -- 19e siècle -- Romans, nouvelles, etc; LITERARY CRITICISM / General; Adultery; Manners and customs; Painters; France; 1800-1899; Fiction